The collected letters of Henry Northrup Castle - Castle, Henry Northrup, 1862-1895 (Ohio University Press ; Samuel N. and Mary Castle Foundation, 2012)
George Herbert Mead, one of America's most important and influential philosophers, a founder of pragmatism, social psychology, and symbolic interactionism, was also a keen observer of American culture and early modernism. In the period from the 1870s to 1895, Henry Northrup Castle maintained a correspondence with family members and with Mead - his best friend at Oberlin College and brother-in-law - that reveals many of the intellectual, economic, and cultural forces that shaped American thought in that complex era. Close friends of John Dewey, Jane Addams, and other leading Chicago Progressives, the author of these often intimate letters comments frankly on pivotal events affecting higher education, developments at Oberlin College, Hawaii (where the Castles lived), progressivism, and the general angst that many young intellectuals were experiencing in early modern America.